2018
DOI: 10.2217/hep-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatments for hepatocellular carcinoma: challenges and future perspectives

Abstract: Sorafenib has been the only approved systemic treatment of hepatocellular carcinoma (HCC) for almost a decade. Recently, two new drugs showed positive results in two Phase III studies. The RESORCE trial identified regorafenib as a valid second-line treatment for patients progressing to sorafenib, the REFLECT trial showed that lenvatinib is noninferior to sorafenib as front-line treatment. Following these trials, the therapeutic scenario will be dominated by anti-VEGFR drugs, with three different molecules show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 84 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…In fact, the possibility of combined HCC-CC appearing as a typical HCC has been reported. This scenario will likely change in the next years as the need for liver biopsies will likely increase due to the increasing number of clinical trials and therapeutic options requiring the identification of biomarkers [76]. Therefore, an increase in the number of identified combined HCC-CC is also likely.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the possibility of combined HCC-CC appearing as a typical HCC has been reported. This scenario will likely change in the next years as the need for liver biopsies will likely increase due to the increasing number of clinical trials and therapeutic options requiring the identification of biomarkers [76]. Therefore, an increase in the number of identified combined HCC-CC is also likely.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the potential mechanisms underlying the AMPK effect on stem-like cells, we analysed some of the signalling pathways associated with development and differentiation in HCC cells transfected with AMPK. Previous studies have reported that the Wnt/ b-catenin signalling pathway is associated with the control of stem cell differentiation (Valkenburg et al, 2011). The activation of this pathway causes the accumulation of b-catenin in the cytosol, which is translocated to the nucleus, where it binds to LEF/ TCF transcription factors and regulates the expression of target genes, including genes involved in differentiation and the cell cycle.…”
Section: Potential Mechanisms Involved In the Ampk Effectmentioning
confidence: 99%
“…The prognosis for patients with advanced HCC remains extremely poor due to the high resistance to cytotoxic therapy. For the past decade, the multikinase inhibitor sorafenib has been the only approved standard treatment for patients with advanced HCC (Kudo, 2017), albeit it only extends life expectancy by 2-3 months (Cheng et al, 2009;Llovet et al, 2008;Tovoli et al, 2018). This can be attributed to the acquisition of resistance, predominantly due to the upregulation of certain survival pathways that may cover up the death signals induced by sorafenib (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to the BCLC algorithm, the treatment of patients with stage C HCC is systemic sorafenib therapy (33). At present, systemic treatment of HCC is evolving rapidly, and three new multikinase inhibitors (i.e., regorafenib, lenvatinib, and cabozantinib) have been shown to be effective in phase 3 clinical trials (34). In the REFLECT trial, lenvatinib has shown to be non-inferior to sorafenib in a front-line setting (35).…”
Section: Advanced-stage Diseasementioning
confidence: 99%